Awareness of Mutual Funds Among Nepalese Investors - Chhetri, Nuwas Kunwar; Bhatt, Sapana (Kshitiz Management Review, 2025)
This study examines the awareness levels of Nepalese investors regarding mutual funds. Employing a descriptive research design, data were collected using self-administered structured questionnaires. The analysis incorporated descriptive statistics, Pearson's correlation, multiple regression, and independent sample t-tests. Results reveal that financial literacy, personal interest, and environmental factors positively influence awareness levels, suggesting that higher prevalence of these variables enhances investor awareness. Furthermore, the independent sample t-test indicates a significant disparity in awareness levels between male and female investors. These findings highlight the need for targeted interventions by policymakers, financial institutions, and educators to bolster financial literacy, cultivate personal interest, and improve environmental conditions. Moreover, addressing gender disparities in financial awareness remains a critical priority to foster inclusivity and informed investment practices. This study provides valuable insights for designing effective strategies to raise awareness of mutual funds and promote equitable financial education among diverse investor groups in Nepal.